MENGEMBANGKAN TOLERANSI BERAGAMA BERBASIS IKLIM KELAS - Tiwi Putria Yosnela; Rahmat Aziz; Esa Nur Wahyuni; M. Samsul Hadi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
School is an important environment for developing the character of religious tolerance in the younger generation. This study aims to reveal the development of students' religious tolerance through classroom climate. This study used a qualitative approach with 6 teachers and 210 students as respondents. Data collection uses interview techniques and questionnaires to measure religious tolerance and documentation—data analysis techniques through data reduction, data presentation, and areas of conclusion/verification. The study results show that students' religious tolerance can be developed through a classroom climate with three conditions, namely a democratic teacher attitude. These learning strategies allow students to work with other students, and class management provides opportunities for each student to participate in class activities. The analysis results also show that there are driving and inhibiting factors in developing religious tolerance. At the end of the discussion, the authors recommend two actions to create a classroom climate that supports the development of religious tolerance: increasing teacher awareness and understanding of religious tolerance and habituating religious tolerance behavior in students.